Music: Social Construction of Reality - อินทร์แก้ว, ชิษณุพงค์ พริก (Journal of Humanities, Social Sciences, and Arts, 2020)
This article aims to understand between people's memories and social phenomena, where music has contributed to the creation of memories for society as a contributor to society by music. Is an influential literature in the practice of discourse in creating meaning. The study primarily aims to identify the patterns of music relationship between people’s memory and social phenomenon. Incorporating a wide range of concepts, notions and theories such as the music, semiotics (signs, symbols and signification), social construction of reality, music or song are systematically exmined.